Study protocol of a clinical randomized controlled trial on the efficacy of an innovative Digital thErapy to proMote wEighT loss in patients with obesity by incReasing their Adherence to treatment: the DEMETRA study - Castelnuovo, Gianluca; Capodaglio, Paolo; De Amicis, Ramona; Gilardini, Luisa; Mambrini, Sara Paola; Pietrabissa, Giada; Cavaggioni, Luca; Piazzolla, Giuseppina; Galeone, Carlotta; Garavaglia, Giacomo; Bertoli, Simona; , the DEMETRA Study Group; et al. (Frontiers in Digital Health, 2023)
Despite the increasing importance of innovative medications and bariatric surgery for the treatment of obesity, lifestyle interventions (diet and physical activity) remain the first-line therapy for this disease. The use of digital devices in healthcare aims to respond to the patient's needs, in order to make obesity treatment more accessible, so our study aims to assess the safety and efficacy of a Digital Therapy for Obesity App (DTxO) for achieving weight loss and its maintenance in patients affected with obesity undergoing an experimental non-pharmacological treatment. Here we present the study protocol of a prospective, multicenter, pragmatic, randomized, double-arm, placebo-controlled, parallel, single-blind study on obese patients who will be treated with a new digital therapy to obtain an improvement in their disease condition through the application of different simultaneous strategies (a dietary regimen and personalized advice program, a tailored physical exercise program, a cognitive–behavioural assessment and program, alerts and reminders, dedicated section on prescribed drugs intake, and chat and online visits with clinical professionals). We believe that DTxO will offer a promising intervention channel and self-regulation tool holding the potentiality to decrease treatment burden and treat more patients thanks to the partial replacement of traditional medical consultation with digital or telephone management, improving self- engagement and reducing the high demands the “obesity pandemic” for both patients and national health services in terms of time, cost, and effort. Clinical trial registration: clinicaltrials.gov, identifier, NCT05394779.